Exploring Toxic Leadership and Its Impact on Employee Well-Being at PT The Univenus - Nuniek Permata; Saripudin Saputra; Suaryo Suaryo; Iis Nurasiah; Andi Hasryningsih Asfar (International Journal Of Economics Social And Technology, 2026)
Employee well-being has become a critical issue in organizational sustainability, particularly in workplaces where destructive leadership behaviors may undermine employees' psychological health and organizational performance. However, studies examining toxic leadership in the context of Indonesian private companies remain limited, highlighting the need for further investigation. This study offers novelty by providing an in-depth qualitative analysis of how toxic leadership affects employee well-being within PT The Univenus. This study aims to explore the phenomenon of toxic leadership and analyze its impact on employee well-being at PT The Univenus. This study uses a qualitative approach with an exploratory case study design to gain an in-depth understanding of the dynamics of destructive leadership in an organizational context. Data were collected through in-depth interviews, non-participatory observation, and document analysis, with purposive sampling used in the selection of informants. Data analysis was conducted using thematic analysis based on Conservation of Resources Theory and Social Exchange Theory. The most significant finding reveals that abusive supervision emerged as the dominant form of toxic leadership, triggering severe psychological distress and burnout among employees while simultaneously reducing organizational trust and increasing turnover intentions. The results indicate that toxic leadership manifests itself in the form of abusive supervision, authoritarian leadership, and manipulative behavior, which significantly negatively impacts employee psychological and emotional well-being. These impacts include increased work stress, emotional exhaustion (burnout), decreased motivation, and weakened social relationships and organizational trust. Furthermore, the findings indicate a lack of follow-up to decreased performance and increased turnover intentions. This study confirms that toxic leadership is a significant factor influencing organizational well-being through the degradation of employee well-being. Therefore, strategic interventions are needed that focus on strengthening leadership quality and creating a healthy work environment.